1985
DOI: 10.1139/v85-499
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase measurements of the influence of stepwise solvation on the kinetics of SN2 reactions of solvated F with CH3Cl and CH3Br and of solvated Cl with CH3Br

Abstract: Flowing afterglow measurements are reported which reveal the influence of stepwise solvation on the nucleophilicity of F− and Cl− in the gas phase at room temperature. The specific rates of nucleophilic displacement reactions with CH3Cl and CH3Br are followed for additions of up to three molecules of solvent for F− solvated with D2O, CH3OH, and C2H5OH and for Cl− solvated with CH3OH, C2H5OH, CH3COCH3, HCOOH, and CH3COOH. The observed precipitous response of the specific rate to solvation is attributed to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 10 publications
6
41
0
Order By: Relevance
“…Our results are especially surprising given the fact that studies of this reaction in water clusters are clearly consistent with the above expectation: As the number of water molecules in the cluster increases, the activation free energy rises monotonically [30][31][32][33][34]. Clearly the water surface introduces an important factor.…”
Section: Reaction Free Energy Profilessupporting
confidence: 56%
“…Our results are especially surprising given the fact that studies of this reaction in water clusters are clearly consistent with the above expectation: As the number of water molecules in the cluster increases, the activation free energy rises monotonically [30][31][32][33][34]. Clearly the water surface introduces an important factor.…”
Section: Reaction Free Energy Profilessupporting
confidence: 56%
“…In general, when considering reactions below the collision controlled limits, the reactions of t-butyl bromide are more rapid than those with t-butyl chloride, and reactions of OH Ϫ (H 2 O) n are more rapid than those of F Ϫ (H 2 O) n , where n ϭ 0, 1. Reaction rates of solvated anions are slower than for bare anions, as observed for S n 2 reactions [16,35]. Specifically, the measured reaction rates are a factor of about three slower for solvated OH Ϫ reacting with t-butyl chloride when compared to bare OH Ϫ .…”
Section: Kinetic Isotope Effectsmentioning
confidence: 64%
“…It is well-known that the rate of some S N 2 reactions is lower by up to 20 orders of magnitude when the reaction is taking place in water compared with the gas phase [6][7][8][9][10][11][12][13][14][15][16][17]. Studies in clusters have demonstrated that the addition of only a few water molecules can have a significant effect on the barrier height [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%